Peningkatan Kualitas Pembuatan Keputusan pada Pengendalian Kemajuan Pelaksanaan Proyek menggunakan Analisis Earned Value - , AGUNG NOEGROHO, Rika Fatimah P.L, ST., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objectives of a project can only be achieved through the work that has been defined in the project plan. Planning and controlling is an important function in project management to achieve the success of a project. Poor infrastructure are proof of the failure of the project that the work is not completed in accordance with project objectives. Delays and cost overruns are one of the major problems encountered in the implementation of the project. So when there is a delay or cost overruns often arises the question whether the project can still be completed according to the planned time or with the remaining funds, project can still achieve benefits. A job can not be separated from the aspects of cost, time and specification and Earned Value Analysis is one of the control techniques that can facilitate these needs for performance monitoring on the progress of project implementation based on work completed on the project planning. Furthermore, based on the performance obtained during the evaluation it can be made final cost estimate and project completion time for projecting future of project. The research was conducted through a case study on Jetty Repair Project PT. Petrokimia Gresik with the project contractors are PT. Multi Eraguna Usaha. Based Earned Value Analysis note that the project has been delayed at week 20 and is expected to experience delays in the completion of the planned time. However, at week 31, the project was accelerated as a result of changes in the scope of work for the project. At week 38 the project is considered complete because the value of the contract has been reached. The thing to be a concern that the changes in the scope of work on the project that is not followed by re-planning, implications for the uncertainty of project financing. Earned Value Analysis showed that the final cost estimates obtained during the evaluation of the project has not met the expectations of project financing. Good project planning is the key to successful application of Earned Value analysis, so that the changes create risks should be managed properly by the company. Earned Value Analysis, when applied as a project control techniques will not only provide information for decision making, but also requires the company to implement the continuous improvement of project management systems, since this technique assesses the performance of the project based on the planned objectives. From the client side, objectives defined in the project plan are the expected benefits and quality, while for contractors that objectives is a specification that must be met. Keywords : Project Management, Decision Support, Quality Improvement, Project Planning, Project Controlling, Earned Value Analysis